Using Adaptive Cross Approximation for Efficient Calculation of Monostatic Scattering with Multiple Incident Angles - Liu, Zhiwei; Chen, Rushan; Chen, Jiaqi; Fan, Zhenhong (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An adaptive cross approximation (ACA) based method is proposed for the fast analysis of the monostatic radar cross-section (RCS). Using the low-rank property, several largest eigenvalues and corresponding eigenvectors of the multiple right hand sides can be computed and saved efficiently by the ACA algorithm. The iterative solution of linear equations is required at these principle eigenvectors. Compared with solving linear equations at each angle repeatedly, the proposed method is able to greatly reduce the computation time. In order to efficiently solve the linear equations, the flexible general minimal residual (FGMRES) iterative solver is applied to compute the coefficients of Rao-Wilton-Glisson (RWG) basis functions. Numerical results demonstrate that the proposed method is efficient for monostatic RCS calculation with high accuracy.